Pedicle Dimensions of the Thoracic Vertebrae in the Zimbabwean Adult Male Population: A Cadaveric Study - Maimoona Khan; Takana Bill Nyamandi; Tapera Makosa (Journal of Rawalpindi Medical College, 2022)
Objective:   To record the dimensions of thoracic-vertebrae pedicles in the grown-up community of Zimbabwe.